Synthesis of Crossover Network Using O′Shea′s Transformation via URC - K. Janchitrapongvej; Vanvisa Chutchavong; Satawat Doungpan; Sudasawan Ngammongkolwong; Pongpan Rattanathanawan; Virote Pirajnanchai (My University, 2024)
This paper describes method of synthesis two-way cross-over network, namely low-pass filter and high-pass filter. Firstly, we introduce synthesis method of obtain all-pass filter. We introduce O′Shea′s transformation ${\bm{P}}( {\bm{s}} ) = {\bm{cosh}}\sqrt {{\bm{SRC}}}$ and Wyndrum′s transformation ${\bm{W}}( {\bm{s}} ){\bm{\ }} = {\bm{\ tanh}}\sqrt {{\bm{SRC}}}$ via uniformly distributed RC ($\overline {{\bm{URC}}}$) network. After obtaining a desired all-pass filter, as an elementary process. We construct low-pass filter and high-pass filter by means of all-pass filter basis. Simulation results MATLAB are carried out and stability are also investigated.
Keywords: Industrial Technology and Control Systems